2017
DOI: 10.1128/jvi.00082-17
|View full text |Cite
|
Sign up to set email alerts
|

The FACT Complex Promotes Avian Leukosis Virus DNA Integration

Abstract: All retroviruses need to integrate a DNA copy of their genome into the host chromatin. Cellular proteins regulating and targeting lentiviral and gammaretroviral integration in infected cells have been discovered, but the factors that mediate alpharetroviral avian leukosis virus (ALV) integration are unknown. In this study, we have identified the FACT protein complex, which consists of SSRP1 and Spt16, as a principal cellular binding partner of ALV integrase (IN). Biochemical experiments with purified recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 60 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…Based on the difference in their preference for distinct chromatin structure we propose that FACT deregulation could induce different and inverted effect depending on the retrovirus as observed by us with HIV-1 and PFV (see Fig. 8 c) and by other authors using ALV model [ 36 ]. These putative functions of FACT on retroviral integration is recapitulated in Fig.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Based on the difference in their preference for distinct chromatin structure we propose that FACT deregulation could induce different and inverted effect depending on the retrovirus as observed by us with HIV-1 and PFV (see Fig. 8 c) and by other authors using ALV model [ 36 ]. These putative functions of FACT on retroviral integration is recapitulated in Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, in vitro integration assays performed in PN templates showed that FACT remodeling activity allowed efficient HIV-1 integration into dense chromatin that was initially refractory to viral DNA insertion. Importantly, this FACT-mediated activation of integration was found to be nucleosome-dependent since no stimulation was detected on naked DNA, in contrast to what was recently observed for ALV [ 36 ]. Our data indicate that FACT generates chromatin structures that are highly preferential for in vitro integration.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Relative to other well studied retroviruses like HIV-1 and MLV, ALV was shown to integrate relatively randomly into the host genomic DNA, with little bias for genomic features [ 4 7 ]. The FACT (facilitates chromatin transcription) complex, a chromatin remodeler, was recently reported to promote ALV integration [ 8 ].…”
Section: Introductionmentioning
confidence: 99%